A woman on the edge of time : a son investigates his trailblazing mother's young suicide - Gavron, Jeremy, 1961- (The Experiment, 2016)
"A forensic reconstruction of novelist and journalist Jeremy Gavron's mother's state of mind, and a portrait of her complex, charismatic short life and of the events that precipitated her suicide when he was only four years old"--Provided by publisher.